Critical analysis of the UNESCO 2003 convention for the safeguarding of intangible cultural heritage through the case of the Hudhud chants of the Ifugao community - Tulagan, Sebastian Benedict B. (Animo Repository, 2022)
The UNESCO 2003 Convention for Safeguarding of the Intangible Cultural Heritage was created to safeguard intangible cultural heritage, to bring awareness to the ICH in a local, national and international domain, to establish respect for the practices of the communities, and to give cooperation and assistance on an international level. The study focuses on the Hudhud chants of the Ifugao community that were inscribed to the UNESCO Representative List of the Intangible Cultural Heritage (ICH) of Humanity in 2008 and proclaimed as Masterpieces of the Oral and Intangible Heritage of Humanity in 2001. However, even with the UNESCO inscription, the Hudhud chants are still considered endangered. The endangerment of the Hudhud chants speculates doubt on the effectiveness of the UNESCO 2003 Convention for the Safeguarding of the Intangible Cultural Heritage in protecting cultural elements. The neoliberal governmentality theory and multi-governance framework theory will be utilized to analyze the endangerment of the chant and the ineffectiveness of the Convention through archival research, fieldwork, and critical discourse analysis. The study aims to conceptualize propositions to assist the stakeholders involved and design an effective mechanism for safeguarding the intangible cultural heritage in the Philippines.